The Role of Non-Disclosure Agreements in Protecting Trade Secret Holders in Micro, Small, and Medium Enterprises (Comparative Study of Indonesian-Azerbaijan Law) - Zahratul Maulida; Ridha Wahyuni (Eduvest - Journal of Universal Studies, 2025)
This research is motivated by the increasing potential for violations of trade secrets by business actors, particularly in the MSME sector, related to information of economic value in the technology and business sectors that is kept confidential. This study aims to understand the legal regulations regarding NDAs as an instrument for protecting trade secrets in Indonesia and Azerbaijan. This research uses normative legal methods and data obtained through library research, analysis of statutory regulations, studies of NDA violation cases in Indonesia, and literature related to the implementation of NDAs in Azerbaijan. The results show that in Indonesia, NDAs are not specifically regulated by law, but have legal force based on the principle of freedom of contract as stipulated in Article 1338 of the Civil Code. Meanwhile, in Azerbaijan, the implementation of NDAs is more effective due to support from government policies and legal institutions that assist MSMEs in maintaining the confidentiality of business information. These findings suggest that strengthening regulations and legal awareness regarding the use of NDAs is necessary to optimize the protection of trade secrets for MSMEs in Indonesia.